2011
DOI: 10.1097/fbp.0b013e3283474a3a
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic synergy of neurotensin receptor subtype 2 agonist NT79 and morphine

Abstract: Neurotensin (NT) is a tridecapeptide with naloxone-independent analgesic action. NT exerts its effects through three molecularly cloned receptor subtypes, NTS1, NTS2, and NTS3. The analgesic efficacy of NT agonists depends on their activation of NTS1 and/or NTS2. NT79 is an NTS2-selective agonist without hypothermic and hypotensive effects, produces analgesic effects in animal models of visceral (writhing), but not thermal (hot plate) pain. This study extends previous study with NT79 to test its efficacy in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 0 publications
5
58
0
Order By: Relevance
“…Since the NTS1-selective (NT72), and non-selective (NT69L) NT agonists attenuate visceral nociception, it is suggested that both NTR subtypes are involved in mediating visceral analgesia and their roles appear to be NT analog dependent (Smith et al, 2012). Additionally, the NTS2-selective analog, NT79, reduces formalin-induced pain and does so in synergy with morphine (Boules et al, 2011a). Further evidence for the involvement of NTS2 in reducing persistent pain comes with the use of knockout mice.…”
Section: Nt and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Since the NTS1-selective (NT72), and non-selective (NT69L) NT agonists attenuate visceral nociception, it is suggested that both NTR subtypes are involved in mediating visceral analgesia and their roles appear to be NT analog dependent (Smith et al, 2012). Additionally, the NTS2-selective analog, NT79, reduces formalin-induced pain and does so in synergy with morphine (Boules et al, 2011a). Further evidence for the involvement of NTS2 in reducing persistent pain comes with the use of knockout mice.…”
Section: Nt and Neuropsychiatric Disordersmentioning
confidence: 99%
“…NT-mediated analgesia has been demonstrated with compounds selective for both the NTS1 and NTS2 receptors as well as nonselective compounds. 23−28 Beyond this, there is now substantial evidence that both NTS1 and NTS2 can mediate relief from chronic or neuropathic pain. 29 This type of pain is difficult to treat with current drugs and does not always respond well to opioid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the NT tridecapeptide, which exerts biological effects by interacting with 2 distinct GPCRs (termed NTS1 and NTS2), has emerged as an important modulator of nociceptive transmission (22)(23)(24)(25). Existing data also indicate that the analgesic effects of NT are independent of the endogenous opioid system (26)(27)(28)(29)(30), and may act synergistically with opioids to reduce pain (31)(32)(33). In the present study, we investigated whether a novel An2-NT conjugate, ANG2002, can access brain parenchyma after systemic administration while retaining the analgesic properties To date, despite substantial investigation, little progress has been made in developing new, effective, and safe analgesics (19).…”
Section: Introductionmentioning
confidence: 99%